Pengaruh Gangguan pada Perubahan Prioritas dan Indeks Konsistensi Matriks Perbandingan Berpasangan dalam Analytical Hierarchy Process - Hanni Garminia; Moh. Hafiyusholeh; Pudji Astuti (Institut Teknologi Bandung, 2010)
A pairwise comparison matrix (PCM) is a matrix arising in Analytical Hierarchy Process (AHP). The application of the AHP as a decision problem tool gives rise to pairwise comparison matrices (PCM). In this work we investigate sufficient conditions on the disturbance which results in reversal of the rank order of the decision alternatives while the PCM Â remains consistent.